2019
DOI: 10.1002/1873-3468.13468
|View full text |Cite
|
Sign up to set email alerts
|

Oncostatin M expression in the mouse uterus during early pregnancy promotes embryo implantation and decidualization

Abstract: Oncostatin M (OSM) is a member of the interleukin‐6 (IL‐6) family, which functions in embryo implantation and decidualization. The expression, function and regulation of Osm in mouse uteri during early pregnancy remain unknown. We show that Osm is mainly expressed in the uterine epithelium from days 1 to 4 of pregnancy and in decidual cells on day 5 of pregnancy. Osm promotes the attachment of Osm‐soaked blue beads, which mimic blastocysts, to a pseudopregnant mouse uterus. Prostaglandin E2 (PGE2)‐induced Osm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 38 publications
(76 reference statements)
0
12
0
Order By: Relevance
“…Immunohistochemistry was performed as described previously [39]. In short, paraffin sections (5 μm) were deparaffined, rehydrated, and antigen retrieved by boiling in 10 mM citrate buffer for 10 min.…”
Section: Methodsmentioning
confidence: 99%
“…Immunohistochemistry was performed as described previously [39]. In short, paraffin sections (5 μm) were deparaffined, rehydrated, and antigen retrieved by boiling in 10 mM citrate buffer for 10 min.…”
Section: Methodsmentioning
confidence: 99%
“…Immunohistochemistry was performed as previously described [ 43 , 44 ]. The paraffin sections (5 μm) were deparaffinized in xylene, rehydrated with a graded series of ethanol, and washed in water.…”
Section: Methodsmentioning
confidence: 99%
“…We also found that sperm cells with abnormal DFI caused a significant increase in OSM expression in the epithelial cells compared with the normal DFI group. OSM, a cytokine from the IL-6 family, is an activator of the JAK/STAT signalling pathway that has an essential role in fertilization, embryo implantation, uterine decidualization and early pregnancy (Fu et al, 2019;Wahl & Wallace, 2001), and its expression by oviduct and endometrial cells was found previously during the interaction of these cell with sperm (Ajdary et al, 2021;Wahl & Wallace, 2001). Activation of this signalling pathway in response to OSM, which is widely expressed throughout the female reproductive tract, was confirmed in cultured human granulosa cells (Pastuschek et al, 2015).…”
Section: Discussionmentioning
confidence: 99%